NATIONAL PLATFORM OF LIFE CYCLE INVENTORY DATABASE IN INDONESIA - Ariyanto, Novy; Sasongko, Nugroho Adi; Eka Putri, Virny Zasyana; Subagyo, Hendro; Siswanto, Siswanto; Wardani, Maya Larasati Donna; Laili, Nurus Sahari; Pratiwi, Annisa Indah; Yanuar, Ahmad Ismed; Septiani, Marini; Hakim, Arif Rahman; Erlambang, Yaumil Putri; Sari, Chintya Komala; Supono, Ihsan; Widiyaningrum, Retno Ayu (ASEAN Journal of Systems Engineering, 2025)
The national Life Cycle Inventory (LCI) database needs to be built, collaborated and integrated to harmonize LCI data, research and information systems across all stakeholders nationally.  The goals of national LCI data harmonization are to: advance national data, research, and information systems by leveraging multi-agency resources and expertise; improve consistency in Life Cycle Assessment (LCA) methods developed by each institution to develop LCA results for decision-making and public disclosure; and enhance public and national institutions to access harmonized data in a standardized searchable format from a common repository. However, the low number of LCI datasets originating from Indonesia results in using other countries' LCI databases that have the potential for high errors and uncertainties and do not represent supply chain data for specific geographical locations in conducting LCA for Indonesian products. The Research Center for Sustainable Production Systems and Life Cycle Assessment (PR SPB PDH) at the National Research and Innovation Agency (BRIN), an institution tasked with establishing a national database for LCI in Indonesia, is currently entering the stage of collecting LCI datasets. This paper proposes recommendations for developing a national platform for the LCI database in Indonesia. The method used is descriptive qualitative analysis from a comparative review of national databases of various countries. The study reveals that the development that has started fulfilled several criteria. However, some requirements must still be met to become a comprehensive LCI national database.